Effect of annealing time and pressure on electrical activation and surface morphology of Mg-implanted GaN annealed at 1300 °C in ultra-high-pressure nitrogen ambient. (26th November 2021) - Sumida, Kensuke; Hirukawa, Kazufumi; Sakurai, Hideki; Sierakowski, Kacper; Horita, Masahiro; Bockowski, Michal; Kachi, Tetsu; Suda, Jun
Abstract: We performed an isothermal annealing study on Mg-implanted GaN at 1300 °C in an ultra-high-pressure (1 GPa) nitrogen ambient. Annealing for more than 30 min resulted in a high acceptor activation ratio and a low compensation ratio that were comparable to those obtained with annealing at 1400 °C for 5 min. We also performed annealing at 1300 °C in a reduced nitrogen pressure of 300 MPa which makes us possible to expand the inner diameter of annealing equipment in the future. High electrical activation, similar to one obtained by annealing at 1 GPa, was successfully obtained.